A new simplified SVPWM algorithm based on modified carrier signal - Garcia,Raymundo Cordero (2011)
This paper presents a simplified algorithm of space vector pulse width modulation (SVPWM) for a two-level three-phase inverter, which can operate in undermodulation and overmodulation modes. In other simplifications founded in literature, the reference voltages are modified and compared with a triangular carrier to estimate the switching states of the inverter. However, this paper proposes the modification of the carrier signal instead of the references. This procedure reduces the number of mathematical operations and increases the execution speed of SVPWM algorithm in DSPs or FPGAs. The reference voltages are sinusoidal, even for overmodulation mode. Simulation and experimental results proves that the proposed simplification produces the same switching patterns than conventional SVPWM, is simpler and is faster than other simplifications.